2015
DOI: 10.1002/anie.201409770
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Amino Acids to Improve the pH Response of pHLIP Insertion at Tumor Acidity

Abstract: The pH-Low Insertion Peptide (pHLIP) offers the potential to deliver drugs selectively to the cytoplasm of cancer cells based on tumor acidosis. The WT pHLIP inserts into membrane with a pH50 of 6.1 while most solid tumors have extracellular pH (pHe) of 6.5-7.0. To close this gap, a SAR study was carried out to search for pHLIP variants with improved pH-response. We learned that (a) replacing Asp25 with α-aminoadipic acid (Aad) adjusts the pH50 to 6.74, matching average tumor acidity, and (b) replacing Asp14 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 48 publications
9
91
1
Order By: Relevance
“…Remarkably, unlike other drug delivery system strategies, pHLIP alone can target tumors, carry cargo and translocate the payload across the plasma membrane without relying on cell receptor interactions or by the formation of pores within the membrane1920. pHLIP has been shown to translocate a plethora of cargo molecules across the plasma membrane into the cytoplasm of cancer cells212223242526, and to target solid tumors as well as metastasis foci in mice26272829. We have also recently shown that pHLIP can target the potent antimitotic monomethyl auristatin E to breast cancer xenographs in mice23.…”
mentioning
confidence: 99%
“…Remarkably, unlike other drug delivery system strategies, pHLIP alone can target tumors, carry cargo and translocate the payload across the plasma membrane without relying on cell receptor interactions or by the formation of pores within the membrane1920. pHLIP has been shown to translocate a plethora of cargo molecules across the plasma membrane into the cytoplasm of cancer cells212223242526, and to target solid tumors as well as metastasis foci in mice26272829. We have also recently shown that pHLIP can target the potent antimitotic monomethyl auristatin E to breast cancer xenographs in mice23.…”
mentioning
confidence: 99%
“…In order to examine the cleavage of disulfide linker on CD123-CPT conjugate, we incubated CD123-CPT with GSH, the most abundant thiol compound in cells, 21,22 since previous studies reported that GSH was able to react with the disulfide linker. 23 After 4 h incubation, the corresponding molecular peak found in the mass spectrum (Fig. S3A) indicated that CPT was successfully released from CD123-CPT conjugates owing to the disulfide linker cleavage.…”
Section: Resultsmentioning
confidence: 97%
“…23 50 μL of the CD123-CPT (11.8 μM) was incubated with 97.5 μL of GSH (18.15 mM in DPBS) at the final concentration of CD123-CPT and GSH is 4 μM and 12 mM. Four hours later, the MW of the mixture was measured with ESI-MS (LTQ Orbitrap, Thermo Fisher Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%
“…They also showed that the replacement of Asp14 with ⊥ ‐carboxyglutamic acid (Gla) increased the sharpness of pH response and the Asp14Gla/Asp25Aad double variant showed pH of 6.79. Additionally, they performed turn‐on fluorescence assays and anti‐proliferation studies using fluorescence labeled and Taxol conjugated Asp14Gla/Asp25Aad variant respectively and showed that the double variant had better cargo delivery capability than WT pHLIP in cancer cells at pH 6.6 . Weerakkody et al.…”
Section: Nanocarriersmentioning
confidence: 99%